If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(c-8)+13=5c+5
We simplify the equation to the form, which is simple to understand
3(c-8)+13=5c+5
Reorder the terms in parentheses
+(+3c-24)+13=5c+5
Remove unnecessary parentheses
+3c-24+13=+5c+5
We move all terms containing c to the left and all other terms to the right.
+3c-5c=+5+24-13
We simplify left and right side of the equation.
-2c=+16
We divide both sides of the equation by -2 to get c.
c=-8
| -4.4=2x+25.6 | | 4.2z=-4(0.6-1.2) | | 2mx^2-mx+1=0 | | 3(6-x)-8=2 | | 5x+6x-64=3x-65 | | 4v-2=10 | | 5x^2=2x+1 | | 6x+19x=25 | | 4x+2+6x-1=13x+1 | | 18-6y=0 | | 4x+3=42 | | 10=3f+1 | | 2b+1=7 | | 4x-5=-1x-30 | | -2x-10+7x=6x+14-4x | | x+14=-32-9 | | -6y+13=-5(y-4) | | 13x=-7-3-20 | | 4x+3x=-35 | | Y+13-7y=-5(y-4) | | 16x+2=-17 | | 22-5x+9x=-2(-6x+5) | | 3y^2+z= | | -33-6y+19=-23y+56+7y | | 7(x+2)=5x+2+6x | | 3x^3-10x^2+50x= | | -2a-9= | | 8(r-2)=r-22+5r | | x*x+x-1=0 | | 9x-4x+3=60 | | x^2+26x+64=0 | | K-14+5k=2(k+3) |